Perbandingan bupivacain 0,5% 15 mg dan fentanil 25 mcg dengna bupivacain 0,5% 15 mg terhadap nilai oksigenasi pada pasien dengan anestesi spinal - Ahmad Ridho Lubis; Rr Sinta Irina; Rommy F. Nadeak; Yuki Yunanda (Poltekkes Kemenkes Aceh, 2023)
Background: Spinal anesthesia is a safe anesthetic technique for elective and emergency surgeries. Spinal anesthesia adversely affects cerebral oxygenation, especially when fentanyl is administered as an adjuvant to spinal anesthesia.Objectives: To determine the difference in cerebral oxygenation values between patients undergoing spinal anesthesia using bupivacaine 0,5% with fentanyl and bupivacaine 0,5% in patients undergoing spinal anesthesia.Methods: This was an analytic post-test experiment with a cross-sectional design. This study was conducted at the Haji Adam Malik Hospital Medan, with a total sample of 36 patients. The research group was divided into groups that received bupivacaine 0,5% 15 mg and bupivacaine 0,5% 15 mg plus fentanyl 25 µg. The rSO2 value was assessed before spinal action (T0), shortly after spinal anesthesia (T1), and 15 min after spinal anesthesia (T2). Near-infrared spectroscopy was used as the measurement instrument. Data to be collected were analyzed with a bivariate, independent T-test and Mann-Whitney test with a 95% confidence interval (CI).Results: The average rSO2 values of patients who received bupivacaine were 64,0% on the right and 65,1% on the right and left sides, respectively. The average rSO2 values of patients who received bupivacaine were 74,8% on the right and 76,1% on the left. There was a significant difference in blood pressure and rSO2 values in patients who received 0,5% bupivacaine spinal anesthesia with 0,5% bupivacaine added to 25 µg fentanyl (p <0,05).Conclusion: There was a significant difference in rSO2 values between patients who received 0,5% bupivacaine spinal anesthesia with 0,5% bupivacaine plus 25 µg fentanyl.